Constitutional Consistency of Indonesia’s Job Creation Law and Its Impact on Regional Autonomy - Yuliasih, Ade; Suding, Sarifuddin; Yassine, Chami; Astawa, I Gde Pantja (Universitas Negeri Gorontalo, 2026)
The enactment of Law No. 6 of 2023 on the Ratification of Government Regulation in Lieu of Law No. 2 of 2022 on Job Creation into law is a legal instrument designed to simplify regulations in order to encourage investment and national economic growth. Nevertheless, this bill has sparked controversy regarding its consistency with the constitutional principles in the 1945 Constitution, especially in terms of local government policy on natural resource management. This study aims to analyze the constitutional consistency of the Job Creation Law and evaluate its legal implications for regional autonomy, particularly in relation to the reduction of local government authority in managing natural resources and policy-making. This study uses a normative legal method with an approach based on laws such as the 1945 Constitution, Law Number 6 of 2023, and Law Number 23 of 2014 on Regional Government. Findings indicate inconsistencies between the provisions of the Job Creation Law and constitutional values related to public participation and workers' rights. A phenomenon of re-centralization of authority has been observed, whereby strategic regional powers such as risk-based licensing (OSS), mining, spatial planning, and environmental supervision have been transferred to the central government. This has resulted in a weakening of regional control functions and a significant decline in Regional Original Revenue (PAD) due to cuts in regional levies. Conclusion The Job Creation Law redefines regional autonomy by placing decentralization under the control of national interests, which has the potential to erode the autonomous identity of regions. Regulatory corrective measures are needed to restore the balance of central-regional relations so that they remain within the constitutional corridor.